Incidence of Muscle Injuries in Soccer Players of a Professional Team: An Analysis before and during the COVID-19 Pandemic - Duque Arias, Mauricio; Agreda Sossa, Jairo; Méndez Galvis, Edgar; Estrada Castrillón, Mauricio; Saldarriaga Franco, Juan; Gallo Villegas, Jaime (Iatreia, 2024)
Introduction: Muscular injuries impose a significant morbidity and economic burden, affecting the sporting outcomes in soccer. The impact of the COVID-19 pandemic on their incidence among professional Colombian soccer players is unknown. Objective: To compare the incidence of muscular injuries in profesional soccer players during the periods of January 2019 to August 2020 (pre-pandemic competition + no competition during pandemic) and September 2020 to December 2021 (competition during pandemic). Methods: A retrospective cohort study across 2019, 2020, and 2021. A robust interrupted time series analysis was conducted to compare the injury incidence between both periods, focusing on changes in slope, level, autocorrelation, and variance. Results: Fifty-two muscular injuries were reported in 94 players. During the pandemic competition period, there was an increase in the level (difference: -12.03; 95% CI -21.13 to -2.93; p-value = 0.01) and in the autocorrelation coefficient (difference: 0.64; p-value = 0.01) of injury incidence proportions compared to the pre-pandemic competition + no competition period. The frequency of severe injuries was higher during the pandemic competition period (2021 season: 57.9%) than in the pre-pandemic competition period (2019 season: 5.0%). During the 2021 season, 63% of the players experienced a COVID-19 infection. Conclusions: The incidence and severity of muscular injuries increased during the competition period amidst the COVID-19 pandemic; a higher number of matches may be one of the ontributing factors.